Association between CARD8 rs2043211 Polymorphism and Inflammatory Bowel Disease: A Meta-Analysis. (April 2015) - Liu, Juan; Liu, Yan-Yan; Liu, Jie; Li, Bao-Zhu; Cen, Han; Xu, Wang-Dong; Leng, Rui-Xue; Pan, Hai-Feng; Ye, Dong-Qing
<x xml:space="preserve">Abstract</x> Objective: The aim of this study was to determine whether caspase recruitment domain-containing protein 8 (CARD8) rs2043211 polymorphism was associated with susceptibility to inflammatory bowel disease (IBD). Methods: Relevant studies were searched using PubMed and Embase up to February 2014. A meta-analysis was conducted on the association between rs2043211 polymorphism and IBD using: (1) allele contrast, (2) the dominant model, (3) the recessive model, and (4) homozygote contrast. The pooled estimated of risk was obtained by random-effects model or fixed-effects model. Publication bias was assessed by Egger's test. Results: Eight relevant articles with a total of 10 534 IBD patients [6785 Crohn's disease (CD), 3713 ulcerative colitis (UC) and 36 indeterminate colitis (IC)] and 6755 healthy controls were included in the meta-analysis, which consisted of 12 studies, 12 for CD, 10 for UC, 2 for IC. There was no significant association between rs2043211 polymorphism and IBD, CD, and IC in overall population. However, stratified meta-analysis by ethnicity showed significant association between rs2043211 polymorphism and CD in the European population under the dominant model [odds ratio (OR) = 1.210, 95% confidence interval (CI) = 1.013–1.445, p = 0.036] and homozygote contrast (OR = 1.212, 95% CI = 1.005–1.461, p = 0.044). Conclusions: Our meta-analysis results indicated significant association between rs2043211 polymorphism and the susceptibility to CD under the dominant model and homozygote contrast in the European population.